2020
DOI: 10.1002/adfm.202000383
|View full text |Cite
|
Sign up to set email alerts
|

Over 15% Efficiency Polymer Solar Cells Enabled by Conformation Tuning of Newly Designed Asymmetric Small‐Molecule Acceptors

Abstract: The prosperous period of polymer solar cells (PSCs) has witnessed great progress in molecule design methods to promote power conversion efficiency (PCE). Designing asymmetric structures has been proved effective in tuning energy level and morphology, which has drawn strong attention from the PSC community. Two hepta-ring and octa-ring asymmetric small molecular acceptors (SMAs) (IDTP-4F and IDTTP-4F) with S-shape and C-shape confirmations are developed to study the relationship between conformation shapes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 53 publications
(46 reference statements)
0
54
1
Order By: Relevance
“…It is known that charge mobility is closely related to molecular packing property of blend films. [ 46,47 ] The grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) characterization was conducted to explore the influence of incorporating Y6‐1O content on molecular packing property of blend films, [ 15,16,48 ] as shown in Figure a. The corresponding out‐of‐plane (OOP) and in‐plane (IP) scattering profiles are shown in Figure 5b,c.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that charge mobility is closely related to molecular packing property of blend films. [ 46,47 ] The grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) characterization was conducted to explore the influence of incorporating Y6‐1O content on molecular packing property of blend films, [ 15,16,48 ] as shown in Figure a. The corresponding out‐of‐plane (OOP) and in‐plane (IP) scattering profiles are shown in Figure 5b,c.…”
Section: Resultsmentioning
confidence: 99%
“…The uniform surface morphologies in the blend films are favorable for the interface contacts at both ends of the active layers, facilitating charge transport and collection. [ 49 ] The AFM phase images show that PBDB‐T:IPT2F‐TT blend features more ordered fibrous phase separation morphology in comparison to two counterparts blends (Figure 4d–f). More homogenous and finer phase separation featuring a bicontinuous interpenetrating network is also observed for PBDB‐T:IPT2F‐TT blend from TEM images (shown in Figure S38, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 2,7 ] It has been found that the introduction of fluorine atoms can reduce the optical bandgap of the resulting acceptor, accompanied by both enhancements in the absorption coefficient and the intermolecular interaction. [ 20,21 ] Thus, the photovoltaic properties of nonfullerene acceptors with fluorinated ending groups can be greatly improved. So far, most of the reported high‐performance acceptors, such as IEICO‐4F, IT‐4F, and Y6, contain fluorinated ending groups.…”
Section: Introductionmentioning
confidence: 99%